Weight training for distance runners - Peditto, M.
Weight training has been a very moot issue when supplemented with a distance training program. Some athletes swear by it, while others totally neglect it. Great Britain's Sebastian Coe, former world record holder in the 800m, was a hard-core weight trainer while others like Kenya's Kip Keino disregarded such exercises. Which of these two athletes is correct? Studies by various groups such as the NCAA have been inconclusive, on average, weight training neither sped them up nor slowed them down. However, weight training does have its benefits, including: an increase overall fitness, a higher level of injury prevention (it increases bone density and muscle mass), and it also makes you look cooler. Listed below are the three types of weight training that a mid-distance/distance runners will use. Among the three, the most important is muscle endurance. In distance events, the bulk of the training load is aerobically performed, because the athletes need to build up and maintain a high level of endurance. With muscle endurance weight training, the athlete is basically fine-tuning and touching up on the work done by their running. By doing such workouts, the athlete can also focus on developing endurance for those muscles neglected in training, primarily located in the upper body.